ANALISIS PENGENDALIAN KUALITAS PRODUK BAJA TULANGAN SIRIP S36 DENGAN MENGGUNAKAN METODE TAGUCHI PADA QUALITY CONTROL - Permana, Fransisco Toebagoes Dias; Wirawati, Sri Mukti; Juniarti, Anita Dyah (Prodi Teknik Industri, Fakultas Teknik, 2024)
PT. Krakatau Osaka Steel is a company engaged in the manufacturing industry which produces Reinforcement Bar, for the product under study, namely S36, which experienced an increase in product defects with dimensions that did not meet standards. The aim of this research is to determine optimal parameters to reduce product defects in S36 products. This research was conducted using the Taguchi method. The Taguchi method can be used in companies to evaluate a process or product that is not yet efficient so that a process or the results of the product produced can be maximized. The setting parameters used are rolling speed (s) and raw material heating time (s), the standards of which have not yet been determined. Data was collected by conducting parameter experiments and analyzed using Minitab 20 software. Based on the research results, it can be concluded that the most influential parameter is rolling speed and the optimal parameter for defective product results with the largest S/N Ratio value is at level 2 for rolling speed. namely -1.915 with a speed of 50 seconds and level 3 for heating time, namely -2.401 with a heating time of 3000 seconds. So, the optimal improvement proposal is to set parameters of 50 seconds for rolling speed and 3000 seconds for heating time.